MiR-21 Is Remotely Governed by the Commensal Bacteria and Impairs Anti-TB Immunity by Down-Regulating IFN-γ - Yang, Fang; Yang, Yi; Chen, Yiwei; Li, Guobao; Zhang, Guoliang; Chen, Lingming; Zhang, Zhiyi; Mai, Qiongdan; Zeng, Gucheng (Frontiers in Microbiology, 2021)
Tuberculosis (TB), which is a frequent and important infectious disease caused by Mycobacterium tuberculosis, has resulted in an extremely high burden of morbidity and mortality. The importance of intestinal dysbacteriosis in regulating host immunity has been implicated in TB, and accumulating evidence suggests that microRNAs (miRNAs) might act as a key mediator in maintaining intestinal homeostasis through signaling networks. However, the involvement of miRNA in gut microbiota, TB and the host immune system remains unknown. Here we showed that intestinal dysbacteriosis increases the susceptibility to TB and remotely increased the expression of miR-21 in lung. Systemic antagonism of miR-21 enhanced IFN-γ production and further conferred immune protection against TB. Molecular experiments further indicated that miR-21a-3p could specifically target IFN-γ mRNA. These findings revealed regulatory pathways implicating intestinal dysbacteriosis induced-susceptibility to TB: intestinal dysbiosis→lung miRNA→targeting IFN-γ→impaired anti-TB immunity. This study also suggested that deregulated miRNAs by commensal bacteria could become promising targets as TB therapeutics.